Placenta‐Derived Mesenchymal Stromal‐Like Cells Promote 3D‐Engineered Muscle Tissue Differentiation and Vessel Network Maturation - Anna Tsukerman; Majd Machour; Margarita Shuhmaher; Eliana O. Fischer; Hagit Shoyhet; Orit Bar‐Am; Gali Guterman Ram; Lior Debbi; Dina Safina; Shulamit Levenberg (Small Science)
Placental‐derived stromal‐like cells (PLX‐PAD) have been shown to facilitate muscle tissue recovery after injury and stimulate angiogenesis. This work assesses the impact of PLX‐PAD cells on the vascularization and maturation of engineered skeletal muscle tissue. Specifically, their effects in direct co‐culture with endothelial cells, pericytes, and myoblasts seeded within microporous 3D scaffolds are characterized. Additionally, the impact of hypoxic PLX‐PAD cell‐conditioned medium (CM) on vascularization and muscle differentiation of engineered tissue is monitored. Co‐culture of PLX‐PAD with myocytes stimulated myocyte differentiation while PLX‐PAD CM promoted the formation of vascular networks. Implantation of a multi‐culture system of vascularized human skeletal muscle tissue and PLX‐PAD into a rectus abdominal defect in nude mice promoted myocyte differentiation, host vessel penetration, and tissue integration. These findings indicate the ability of placenta‐derived cells to induce the formation of vascularized engineered muscle constructs with potential therapeutic applications.